Vascular variant of Eagle syndrome: a review - Tadjer, Joy; Béjot, Yannick (Frontiers in Neurology, 2024)
Eagle syndrome is defined as an elongated styloid process (ESP) that compresses nearby vasculonervous structures. Vascular variant of Eagle syndrome can lead to neurological symptoms including syncope, transient ischemic attack or stroke, but other atypical presentations have been described, which can make its diagnosis challenging. This review aimed to depict the characteristics of patients with symptomatic vascular variant of Eagle syndrome. The literature search identified 56 reported cases of vascular variants of Eagle syndrome, with a mean age at onset of 51 years (range: 15-85 years), and a male-to-female ratio was 2.4. ESP was bilateral in 63% of cases and mean length was 48 mm (range: 31-77 mm). Vascular complications were mostly represented by internal jugular vein (IVJ) stenosis (n=28), followed by internal carotid artery (ICA) dissection (n=15). Eight cases of ICA thrombosis and two cases of severe chronic stenosis of ICA >90% were also described. Vascular complications may lead to cerebral ischemia due to either a thromboembolic mechanism or less frequently low blood flow.A laminar cortical necrosis as a cerebral complication of ICA compression was exceptionally described in one case, and such atypical clinical presentation may be regarded as a diagnostic pitfall.